Association of self-reported dental caries with sex, lifestyle, and problematic Internet use among elementary school children in Japan - Masaaki Yamada; Michikazu Sekine; Takashi Tatsuse; Yukiko Yanai (BMC Oral Health)
Abstract Background Dental caries is the most prevalent disease in elementary schoolchildren in Japan. Problematic Internet use (PIU) has increased among children; however, its association with caries has rarely been studied. We aimed to explore (1) sex differences in dental caries and (2) the association of dental caries with lifestyle and PIU among elementary school children in Japan. Methods From 110 elementary schools in Toyama Prefecture, 13,413 children in the 4th-6th grades (mean age, 10.5 years) participated in the Toyama Safe Internet Use Project in 2018. We inquired about lifestyle, anthropometric data, family rules for screen time, PIU, and the number of self-reported treated caries. PIU was assessed using the Young’s Diagnostic Questionnaire. We defined children having ≥ 3 caries as having multiple caries. Subsequently, a modified Poisson regression analysis was performed. Results Overall, 12,146 children (90.7%) were analyzed. The prevalence of multiple caries was 25.7% (24.4% in boys and 27.0% in girls). In the regression analysis, the presence of multiple caries was significantly associated with being a girl(adjusted prevalence ratio (aPR) 1.13), being in higher grades (5th grade: aPR 1.13 and 6th grade: aPR 1.14), skipping breakfast (aPR 1.11), having late bedtime (10 to 11 p.m.: aPR 1.17 and ≥ 11 p.m.: aPR 1.23), tooth brushing (once a day: aPR 1.14 and not every day: aPR 1.41), having no family rules (aPR 1.20), and PIU (YDQ score 3–4: aPR 1.17). When stratified by sex, a dose-response relationship was observed between PIU and the presence of multiple caries in boys (YDQ score 3–4: aPR 1.19 and YDQ score ≥ 5: aPR 1.22). Conclusion Being a girl, having an undesirable lifestyle, and PIU were significantly associated with multiple self-reported caries. In addition to a having a healthy lifestyle, restricting PIU is recommended to prevent caries in children.